Financial economics - Fabozzi, Frank J. (Wiley, 2011)
Financial Economics has quickly established itself as a strong and growing market. Financial Economics by Frank Fabozzi, Ted Neave, and Gaofu Zhou presents an introduction to basic financial ideas through a strong grounding in microeconomic theory. This calculus based text explores the theoretical framework for analyzing the decisions by individuals and managers of firms, and area which is common to both the financial economics and microeconomics. It also explores the interplay of these decisions on the prices of financial assets.
Includes bibliographical references and index. - Print version record
Keywords: Finance; Economics; Finances; Économie politique; finance; economics; BUSINESS & ECONOMICS / Economics / General